Behaviour of the extended Toda lattice - Wattis, Jonathan A.D.; Gordoa, Pilar R.; Pickering, Andrew (Elsevier, 2015)
We consider the first member of an extended Toda lattice hierarchy. This system of equations is differential with respect to one independent variable and differential-delay with respect to a second independent variable. We use asymptotic analysis to consider the long wavelength limits of the system. By considering various magnitudes for the parameters involved, we derive reduced equations related to the Korteweg-de Vries and potential Boussinesq equations.